Surveillance in Children and Adolescents with von Hippel-Lindau (VHL)-Related Pheochromocytomas and Paragangliomas: A Survey of MET and Freiburg-VHL Registries in Germany (Journal of Kidney Cancer, 2024)
Early identification of patients at risk with von Hippel-Lindau (VHL) syndrome-related pheochromocytoma and paraganglioma (PPGL) is crucial to prevent morbidity. We investigated the current surveillance recommendations in VHL-related PPGL in children and adolescents. German Pediatric Oncology and Hematology–Malignant Endocrine Tumor registry (GPOH-MET) and Freiburg-VHL registry (1996–2022). In all, 75 patients (aged 0–18 years) with VHL syndrome were analyzed and 52 were in the Freiburg screening/surveillance program (median follow-up: 11.5 ± 0.94 years), including annual hormone level measurements, eye examination (starting at the age 6 years), and MRI of the abdomen and central nervous system (CNS) (starting at the age of 12 years). Retrospective analysis of clinical outcomes and descriptive statistics was performed. Of the 75 patients, 60 had a previous clinical diagnosis of PPGL with subsequent genetic testing, and 63% had a positive family history. In spite of having positive family history, large variations of timings between genetic and clinical diagnosis (range: -9 to +40 years) were observed. The mean age of first PPGL was 12.4 ± 0.41 years (range: 4–18 years). Recurrence of PPGL was common (46%; range: 2–7 per patient), and that of other tumors occurred: hemangioblastomas (73%), retinal angiomas (58%), renal cell carcinomas (21%), and pancreatic neuroendocrine tumors (12%). VHL-related PPGL appeared by the age of 12 and recurrences were observed frequently. Hemangioblastomas and retinal angiomas were common. In spite of a positive family history, VHL diagnoses were delayed. Because of high tumor proportions of affected families with children, it needs an optimization of the surveillance framework to enhance compliance and minimize anxiety and worse disease outcomes.